Carbon Footprint Analysis of Broadacre Livestock Grazing Systems in Southern Australia - Gale, Danielle (Curtin University, 2020)
This research examined the carbon footprint of sheep and beef cattle production in south-western Australia, with focus on the impact of different pasture systems. Carbon footprint frameworks were developed to enable the inter- and intra-farm scale examination of livestock production systems and identification of strategies with mitigation potential. Perennial pasture, along with improved reproductive and grazing management practices, were identified as promising options to reduce the carbon footprint of livestock production in southern Australia.